Answer:
Option 3
Explanation:
Option 1
f(a) = a² - 4
g(a) = √a
(gof)(a) =
![\sqrt{a^(2)-4}](https://img.qammunity.org/2021/formulas/mathematics/high-school/la5apno9aqw82nrtjrjtrd11sx3wmfhx1w.png)
Option 2
f(a) =
![(1)/(2)a-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/46hduu86pgazgri67cr0qfrq9yh94gr1sz.png)
g(a) = 2a - 2
(gof)(a) =
![2[(1)/(2)a-1]-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/ppkz309bln1g8eio4livnodvdm28aolzsc.png)
= (a - 2) - 2
= a - 4
Option 3
f(a) = 5 + a²
g(a) =
![√((a-5))-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/84shggrr2toj72ekonmu9m67esifv7ts6t.png)
(gof)(a) =
![√((a^2+5-5))-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/qbo3a4th7ofbqd3u2iou3fffnxcyzsn7y4.png)
= |a| -2
Option 4
f(a) = 3 - 3a
g(a) = 4a - 5
(gof)(a) = 4(3 - 3a) - 5
= 12 - 12a - 5
= 7 - 12a
Therefore, Option 3 is the answer.